EFEK PERTUMBUHAN EKONOMI, KEPENDUDUKAN, DAN TRANSPORTASI TERHADAP KUALITAS UDARA SUMATERA SELATAN - Nukke Anastasya; Endan Suwandana (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2022)
The economic growth of an area affects the environmental quality of the area. This study aims to analyze the effect of economic growth, population, and transportation variables on the Air Quality Index (IKU) in South Sumatra. This study uses panel data of Regencies in South Sumatera as a cross section. The analytical method used in this study is panel data regression with Random Effect Model (REM) to explain the factors that influence Air Quality Index (IKU). The results of this study show that Gross Regional Domestic Product per capita (GRDP Per Capita), population density, and the ratio of road length have a significant effect on the Air Quality Index. Population growth that followed by economic activity growth caused the increase of environmental degradation. Government policies the related to regulations in the field of environmental management and the use of IT by digitizing the use of resources is needed to help deal with environmental issue.